External debt : Definition, Statistical Coverage and Methodology. (International Monetary Fund, 1988)
This book is intended to provide the user of debt statistics with a comparative description fo the statistics collected by the Bank for International Settlements, the International Monetary Fund, the Organization for Economic Cooperation and Development, and the World Bank. It discusses how these statistics are gathered, why they take the form they do, and how they relate to each other.